Immersive Learning for Arabic as a Foreign Language: A VR Game-Based Model for Vocabulary Acquisition - Fitri Nurul'ain Nordin; Abdul Azim Mohamad Isa; Tg Ainul Farha Tg Abdul Rahman; Fariz Azzuan Mat Suparia (RSIS International, 2026)
Tier 2 (Index by ERA)